Personal culture as a goal of continuing developmental education: Philosophical and methodological substantiation - N. L. Hudyakova; A. B. Nevelev; V. S. Neveleva (Образование и наука)
Introduction. The article presents a philosophical and methodological substantiation of personal experience as a subject of development in the educational process and personal culture as the goal of developmental education. Such a justification is the content of philosophy of developmental education in that part, which can be attributed to philosophical anthropology, to the philosophy of culture and social philosophy. This content is made up of knowledge about the laws governing the development of a personal experience and the formation of the main types of personal culture. It allows us to determine the invariant structure of educational goals, which can be correlated with the requirements for educational outcomes described through competences. On the basis of the invariant system of developmental education goals, variable ways of achieving these goals, both for general and for vocational education, can be determined, reflecting the particular and individual levels of human existence.The aim of the present article is to philosophically substantiate the understanding of personal culture as the goal of education, focused on the development of a person as a whole, on the development of the personality.Methodology and research methods. The methodological basis of the study is the dialectical approach: the dialectic of the essence and existence of a person, the principle of unity of diversity, the relationship of general, particular and individual. Research methods were determined in accordance with philosophical and psychological knowledge about a person, obtained on the basis of applying systematic, subject-active and cultural-historical approach.Results. The result of the study was the conclusion that the laws of acquisition, reproduction and development of a personal experience are the objective basis for determining the system of goals of developmental education, its content and the complex of ways to organise it. Personal experience is the subject of development in the process of education. The qualitative state of experience, which characterises the completion of the stages of the social and cultural development of a person, is defined by the authors as personal culture. It acts as a complete product of the educational process, and therefore the overall goal of education. Knowledge of the laws of existence and development of the basic elements of personal social and cultural experience becomes the rationale for determining the goals, content and methods of organising education and training in a holistic educational process.Scientific novelty. The scientific novelty of the study lies in the fact that for the first time in the philosophy of education, the authors consider the formation of personal culture in conjunction with the development by individuals of groups of cultural means corresponding to the main stages of human cultural development.Practical significance. The developed approach allows for the determination of the invariant structure of pedagogical technologies of continuing developmental education, as well as this approach involves the creation of a variable component of technology, ensuring the unity and originality of the levels of human existence in the educational process.